Tufts 1984 women's volleyball team - Unknown (Tufts Archival Research Center, 2014)
8 x 10 in., photographic print. Back of print reads: "TUFTS 1984 WOMEN'S VOLLEYBALL TEAM; Record: 18-7-1; Front row: (left to right) Dana Mischell (5), Sandra Wang (7), Sara Niedermeyer (1), Julie Bernel (11), Sylvia Congett (3); Back row: (left to right) Assistant coach Tracy D'Allesandro, Melissa Needle (15), Lyssa Keusch (6), Jennifer Overholt (13), Linda Amoroso (14), Kathy Amoroso (12), Karen Spiegel (9), Shona Glilnk (4), Malia Enright (8), Coach Bob Fareau